2020
DOI: 10.21203/rs.3.rs-59677/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Process Evaluation of the Sophia Step Study-A Primary Care Based Three-Armed Randomized Controlled Trial Using Self-Monitoring of Steps With and Without Counseling in Prediabetes and Type 2 Diabetes

Abstract: Background Describing implementation features of an intervention is required to compare interventions and to inform policy and best practice. The aim of this study was to conduct a process evaluation of the first 12 months of the Sophia Step Study: a primary care based RCT evaluating a multicomponent (self-monitoring of daily steps plus counseling) and a single component (self-monitoring of steps only) physical activity intervention to standard care on cardiometabolic health. Methods The evaluation was guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The response rate of invited and eligible individuals was 49%. A process evaluation with details on the context, reasons for declining and adherence to the intervention has been published elsewhere [20]. Figure 1 depicts the number of participants recruited, excluded, declined, consented and dropouts per intervention group, as well as reasons for exclusion and termination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The response rate of invited and eligible individuals was 49%. A process evaluation with details on the context, reasons for declining and adherence to the intervention has been published elsewhere [20]. Figure 1 depicts the number of participants recruited, excluded, declined, consented and dropouts per intervention group, as well as reasons for exclusion and termination.…”
Section: Resultsmentioning
confidence: 99%
“…Although of varying lengths and support intensity, other similar trials reported superior effects in intervention groups receiving step counting and counselling versus step counting alone [44][45][46]. A process evaluation of the Sophia Step Study has been undertaken, providing details of the intervention delivery and context, as well as evidence for feasibility and a high degree of reach of the interventions [20]. Thus, the lack of intervention effect in this study cannot be explained by unsuccessful intervention delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The randomised controlled trial (RCT) of the first year of the Sophia Step Study measured the change in physical and behavioral activity at a baseline of 6 and 12 months by accelerometry as daily steps. This was the three-armed RCT study assessing pedometers and the tools for self-considering of stepping containing and excluding by monitoring the health care professionals on cardiac condition and getting HbA1c as a primary outcome evaluated pre and post-study [22].…”
Section: Reviewmentioning
confidence: 99%